Porous Silicon-Based Gas Sensors and Miniature Hydrogen Cells - Dzhafarov, Tayyar; Yuksel, Surevya Aydin; Lus, Cigdem Oruc (IOP PUBLISHING LTD, 2008)
The current-voltage (I-V) characteristics of Au/porous silicon (PS)/Si Schottky-type structures in humid, CO, and H2S gas atmospheres were investigated. It was found that the gas atmosphere influences the I-V characteristics, particularly the reverse current in Au/PS/Si and Au/PS structures. The reverse current in the H2S atmosphere was 103 times larger than that in room-temperature (300K) air [45% relative humidity (RH)]. The generation of an open-circuit voltage (up to 480 mV) at the Au/PS interface in humid, CO, and H2S atmospheres was detected. The humidity- and gas-stimulated effect of voltage generation in the Au/PS/Si structures was reversible with a response time of 60s. The quite high sensitivities to humidity, CO, and H2S (about 9 mV/RH, 4mV/ppm, and 2mV/ppm, respectively) indicate the possibility of using the obtained Au/PS/Si structures as both gas sensors and miniature hydrogen fuel cells. The mechanism for the gas-stimulated generation of electricity in the Au/PS structures is discussed and is considered to be similar to that of the proton exchange membrane in hydrogen fuel cells. [DOI: 10.1143/JJAP.47.8204]
Keywords: porous silicon; Schottky-type structure; gas sensor; CO; H2S; hydrogen fuel cell; HUMIDITY-VOLTAIC CHARACTERISTICS; PS-SI STRUCTURES; Physics